Association between ApoA1, ApoB, and the ApoB/ApoA1 ratio with the risk of diabetic neuropathy: A systematic review and meta-analysis - Gosal, Ervina; Djuartina, Tena; Sutrisno, Alfred; Budianto, Iskandar R. (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Diabetic neuropathy is a common complication of diabetes mellitus and a major contributing factor to the development of diabetic foot ulcers (DFU). Apolipoproteins A1 (ApoA1) and B (ApoB), as well as the ApoB/ApoA1 ratio, play a crucial role in lipid metabolism and are believed to be involved in the development of neuropathic damage in individuals with diabetes. This study highlights the association between ApoA1, ApoB, and the ApoB/ApoA1 ratio with the risk of developing diabetic neuropathy. A systematic review was conducted following the PRISMA guidelines. An extensive literature search was conducted on December 7, 2024, using multiple databases, including PubMed, ProQuest, EBSCOhost, and Medline. There were no language or publication date restrictions. This synthesis relied solely on odds ratios (ORs) with 95% confidence intervals (CIs) as effect sizes. Included studies were observational in design, examining the association between ApoA1, ApoB, or the ApoB/ApoA1 ratio with diabetic neuropathy in an adult population. Of the 320 studies identified, 5 met the criteria for inclusion in the qualitative synthesis and meta-analysis, involving 2,756 diabetic patients. Findings showed higher ApoB levels and lower ApoA1 levels in patients with diabetic neuropathy compared with controls. However, no significant association was found between ApoB, ApoA1, or the ApoB/ApoA1 ratio with diabetic neuropathy or DFU risk. This review found no significant association between ApoB, ApoA1, or the ApoB/ApoA1 ratio with diabetic neuropathy or DFU. Further research is needed to explore their potential role in DM complications.